Novel 1,2,3-Triazole Erlotinib Derivatives as Potent IDO1 Inhibitors: Design, Drug-Target Interactions Prediction, Synthesis, Biological Evaluation, Molecular Docking and ADME Properties Studies - Xu, Gui-Qing; Gong, Xiao-Qing; Zhu, Ying-Ying; Yao, Xiao-Jun; Peng, Li-Zeng; Sun, Ge; Yang, Jian-Xue; Mao, Long-Fei (Frontiers in Pharmacology, 2022)
Indoleamine 2, 3-dioxygenase 1(IDO1) plays a predominant role in the cancer immunotherapy which catalyzes the initial and rate limiting step of the kynurenine pathway as a key enzyme. To explore novel IDO1 inhibitors, 5 erlotinib-linked 1,2,3-triazole derivatives were designed by using structure-based drug design strategy. Drug-target interactions (DTI) were predicted by DeePurpose, an easy-to-use deep learning library that contains more than 50 algorithms. The DTI prediction results suggested that the designed molecules have potential inhibitory activities for IDO1. Chemical synthesis and bioassays showed that compounds exhibited remarkable inhibitory activities against IDO1, among which compound e was the most potent with IC50 value of 0.32±0.07 μM in the Hela cell assay. The docking model and ADME analysis exhibited that the effective interactions of these compounds with iron of heme and better drug-likeness ensured the IDO1 inhibitory activities. The studies suggested that compound e was a novel interesting IDO inhibitor for further development.